Editorial - Merino-Soto, César (2023)
The content of the title of this special issue is sufficiently descriptive of what is expected: a content focus on educational and psychological assessment instrumentation and practices in the context of higher education. Psychoeducational assessment is generally understood as a comprehensive action focused on the specific context of education, with the ultimate goal of creating interventions matched to the needs of students (Isaacs et al., 2013). However, in the evaluation processes in higher education, aspects ranging from the admission process are also included, to continue with the student life cycle (Halpern & Butler, 2013). And thematically, educational assessment in general, and in higher education in particular, cannot be understood solely as a set of manuscripts for developing and adapting measures.